The effects of passive tobacco smoking on the microcirculation of the abdominal wall in rats - Sandler,Paulo (2016)
ABSTRACT PURPOSE: To analysis the effects of passive smoking on the microstructure of tissues of the abdominal wall regarding microcirculation, using histopathological study of the tobacco exposed rats. METHODS: Twenty four male Wistar rats were divided in Control Group (CG = 8 animals) and Exposition Groups (EG = 16 animals). EG was exposed to cigarette smoke 4x/day for 120 days, while CG was preserved from exposure. Food, water and housing were similar for both groups. After 120 days, urine samples were collected before necropsy to analyze cotinine levels (ng/mL) in urine and blinded histopathological analysis of the abdominal wall performed to count arteries and veins in dermal and muscular fascia layer. RESULTS: No difference in weight was observed between both groups (P>0.05). Cotinine concentration was significantly higher in EG (P<0.05). In dermal layer, the average of vessels per animal was 8.72 (IC95%: 8.31-9.13) for CG and 11,23 (IC95%: 10.09-12.38) for EG. In muscular fascia layer the average of vessels per animal was 17.97 (IC95%: 15.79-20.15) for CG, whereas the average for EG was of 14,85 (IC95%: 12.71-17.01) (P<0.05). CONCLUSION: Exposition to passive smoking may cause increase in the number of vessels in dermal layer, with the opposite effects at the muscular fascia layer.